2016
DOI: 10.1097/med.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eicosapentaenoic acid and docosahexaenoic acid on lipoproteins in hypertriglyceridemia

Abstract: Purpose of reviewThe treatment of hypertriglyceridemia (HTG) with v-3 fatty acid preparations adds a novel therapy to reduce cardiovascular disease. This review examines the effects of eicosapentaenoic acid (EPA) and docosahexaenoic acid on lipoproteins and the cardioprotective effects in HTG. Recent findingsThe evidence that v-3 fatty acid therapy at prescription strength is effective and safe at lowering triglyceride levels is growing. Although EPA/docosahexaenoic acid formulations did lower triglyceride lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The epoxide metabolites of ω-3 PUFAs (e.g., EDPs) were reported sporadically regarding their biological functions although ω-3 PUFAs, such as DHA and eicosapentaenoic acid (EPA), as well as DHA-and EPA-enriched foods, have been reported and reviewed extensively to be antiinflammatory, cardio-protective, reno-protective, and tumor inhibitory (10,(19)(20)(21)(22)(23)(24). Sharma et al (12) reported recently that 19 (20)-EDP significantly reduced renal fibrosis in a murine model of unilateral ureteral obstruction (UUO)-induced uremia.…”
Section: Discussionmentioning
confidence: 99%
“…The epoxide metabolites of ω-3 PUFAs (e.g., EDPs) were reported sporadically regarding their biological functions although ω-3 PUFAs, such as DHA and eicosapentaenoic acid (EPA), as well as DHA-and EPA-enriched foods, have been reported and reviewed extensively to be antiinflammatory, cardio-protective, reno-protective, and tumor inhibitory (10,(19)(20)(21)(22)(23)(24). Sharma et al (12) reported recently that 19 (20)-EDP significantly reduced renal fibrosis in a murine model of unilateral ureteral obstruction (UUO)-induced uremia.…”
Section: Discussionmentioning
confidence: 99%
“…7 Dietary intervention offers an alternative with potential benefits over currently available treatments for atherosclerotic dyslipidemia. 8 Several animal studies have demonstrated that seafood and marine byproducts exert strong cholesterol-lowering and lipid-regulating effects. Lamaziere et al 9 found that prolonged feeding with eicosapentaenoic acid (EPA)-and docosahexaenoic-acid-enriched fish oil decreases hepatic fat levels and ameliorates non-alcoholic fatty liver disease prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia is a major risk factor for atherosclerotic cardiovascular disease (ASCVD), although contrasting observations have been reported. , Statin therapy is effective for lowering low-density lipoprotein (LDL) levels; however, side effects, including central nervous system complaints, have been reported . Dietary intervention offers an alternative with potential benefits over currently available treatments for atherosclerotic dyslipidemia . Several animal studies have demonstrated that seafood and marine byproducts exert strong cholesterol-lowering and lipid-regulating effects.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the effect of omega-3 fatty acids on CV outcomes is unknown, but two randomized outcome trials, REDUCE-IT and STRENGTH, are assessing additional risk reduction when statins are combined with omega-3 fatty acid therapy. 10,11 In general, treatment with 2-4 g of a prescription-grade omega-3 fatty acid formulation, containing mainly EPA and/or DHA, reduces serum TG levels by approximately 30%. 3,5 Omega-3 fatty acids reduce serum TG levels by decreasing VLDL production rates, while VLDL clearance rates are less consistently affected.…”
Section: Introductionmentioning
confidence: 99%